Racial Discrimination in Christina Hammond Reed’s The Black Kids (Sastra Inggris UNPAM, 2025)
This study is aimed to analyzing the issue of racial discrimination represented in novel experienced by the main character in The Black Kids (2020), a novel by Christina Hammonds Reed. Every problem experienced by the main character concerns the issue of racial discrimination. In conducting the analysis, this study uses qualitative research (Creswell, 2012) by identifying the issue and presenting the results in form of text and using concepts about race (Delgado and Stefancic, (2001). The Black Kids is about a seventeen-year-old girl who experienced racial discrimination and she had to experience living during a black rebellion in the city. As a teenager, it became an unfortunate reality, but the incident made her become brave and more understanding about who she was, thus making her become herself. The result of this research showed that the changing personality of the main character who initially ignore become aware of the surrounding to able coexist with whites. The author explores and describes social conditions, discrimination, and life experiences of black people.